The advertisement call of Brachycephalus alipioi (Anura: Brachycephalidae), a pumpkin toadlet from Espírito Santo, Brazil - Borges, Jayni Santos; Gasparini, João Luiz; Almeida, Antonio De Padua; Toledo, Luís Felipe; Dena, Simone (Zootaxa, 2025)
The advertisement call is a primary form of acoustic communication in anurans, crucial for intraspecific recognition and species identification during the breeding season. Bioacoustic data, however, remain scarce for taxonomically complex groups such as the genus Brachycephalus. Brachycephalus alipioi is an aposematic species endemic to the state of Espírito Santo, Brazil, occurring in the municipalities of Vargem Alta (type locality), Forno Grande, Santa Teresa, and Domingos Martins. It is currently the only described species of the genus in this region. Herein, we provide the first description of its advertisement call and compare it with members of the B. vertebralis and B. ephippium groups, based on available literature. Calls from two recordings of B. alipioi were analyzed using a note-centered approach. The advertisement call has a pulsatile structure, with a mean dominant frequency of 4.05 ± 0.14 kHz and an average of 7.95 ± 1.56 pulses per note, produced at a rate of 3.61 ± 0.1 notes/s. Approximately 66% of the notes consist of eight or nine pulses. These data expand the acoustic knowledge of Brachycephalus and contribute to understanding communication in an endemic species of the Atlantic Forest, a global biodiversity hotspot.